CD200R1 regulates eosinophilia during pulmonary fungal infection in mice. Issue 9 (7th August 2019) - Salek‐Ardakani, Samira; Bell, Thomas; Jagger, Christopher P; Snelgrove, Robert J; Hussell, Tracy
Abstract: CD200 receptor 1(CD200R1) signalling limits myeloid cell responses and reduces autoimmunity, alloimmunity and viral‐mediated immunopathology, but has never been examined in the context of eosinophilic inflammation. Susceptibility to lung fungal infection is associated with T‐helper 2 (Th2) cytokine dominated responses and strong eosinophilic pathology. Blockade of CD200R1 enhances type I cytokine responses in many infectious and non‐infectious settings and so may promote a more protective response to fungal infection. By contrast, we demonstrate that, rather than promoting type I cytokine responses, CD200R1 blockade enhanced eosinophilia in a mouse model of Cryptococcus neoformans infection, whereas CD200R1 agonism reduced lung eosinophilia – with neither strategy completely altering fungal burden. Thus, we reveal a surprising disconnect between pulmonary eosinophilia and cryptococcal burden and dissemination. This research has 2 important implications. Firstly, a lack of CD200R1 signalling enhances immune responses regardless of cytokine polarisation, and secondly reducing eosinophils does not allow protective immunity to develop in susceptible fungal system. Therefore, agonists of CD200R1 may be beneficial for eosinophilic pathologies. Abstract : In homeostasis the lung microenvironment is controlled by CD200 on T and epithelial cells binding to CD200R on macrophages (Top). During fungal infection the interaction between CD200 and CD200R is reduced allowing inflammation that results in eosinophilic lung disease (middle). Blockade of CD200 or CD200R causes enhanced eosinophilic disease. This implies that the interaction between CD200 and CD200R is required to limit eosinophilic inflammation.